2022
DOI: 10.3389/fonc.2022.809589
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IGF2BP2 Promotes Oral Squamous Cell Carcinoma Progression That Is Related to Cell Proliferation, Metastasis and Tumor-Infiltrating Immune Cells

Abstract: The strong invasive and metastatic abilities of oral squamous cell carcinoma (OSCC) cells in the early stage are the main reason for its poor prognosis. The early diagnosis and treatment of OSCC may reduce the metastasis rate and improve the survival rate. The aim of this study was to explore candidate biomarkers related to the prognosis and progression of OSCC. We performed weighted gene coexpression network analysis to identify key modules and genes associated with OSCC and intersected the differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Univariate and multivariate analyses both identified IGF2BP2 expression, histological grade, T status, lymph node metastases, and disease stage as key independent prognostic factors impacting the overall survival of OSCC patients (Table 3 ). Our findings suggest that IGF2BP2 may operate as an oncogene in OSCC cells, which is in line with earlier research 34 , 35 . Note that this was the first study to examine the use of clinicopathological variables and IGF2BP2 protein expression within the context of OSCC prognosis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Univariate and multivariate analyses both identified IGF2BP2 expression, histological grade, T status, lymph node metastases, and disease stage as key independent prognostic factors impacting the overall survival of OSCC patients (Table 3 ). Our findings suggest that IGF2BP2 may operate as an oncogene in OSCC cells, which is in line with earlier research 34 , 35 . Note that this was the first study to examine the use of clinicopathological variables and IGF2BP2 protein expression within the context of OSCC prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…We also determined that IGF2BP2 overexpression is related to poor overall survival outcomes in OSCC patients (Figure 2 ), which suggests that it could perhaps be used as a prognostic indicator for use in OSCC risk classification. Elevated IGF2BP2 expression in OSCC cells has been linked to cell proliferation, metastasis, and tumor-infiltrating immune cells in in vitro experiments 34 . Those studies confirm our clinical results, which suggest that IGF2BP2 enhances OSCC epithelial cell proliferation and epithelial-mesenchymal transition (EMT), thereby promoting tumor growth and invasion in OSCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 53 We first found that IGF2BP2 directly bound to the m6A sites in the CTSL 5′‐UTR and enhanced CTSL mRNA stability in an m6A‐dependent manner. Previous studies have shown that increased IGF2BP2 expression levels promote the metastasis of oral squamous cell carcinoma 54 and gastric cancer. 55 Here, we revealed the oncogenic role of IGF2BP2 in cervical cancer metastasis and its regulatory effect on CTSL mRNA stability to enhance cervical cancer progression.…”
Section: Discussionmentioning
confidence: 96%